ANALISIS YURIDIS HAK TANGGUNGAN DIATAS HAK GUNA BANGUNAN BERASAL DARI HAK PENGELOLAAN ASET PEMERINTAH DAERAH (Studi di Perumahan Korpri Jalan Jakarta Loa Bakung Samarinda) - Yulia Eka Saputri (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
ABSTRACTLand rights in Indonesia are divided into 2 major parts, namely (1) permanent land rights such as property rights, building use rights, and business use rights. (2) Land rights that are not permanent such as Mortgage Rights (formerly called Hypotheek), Mortgage Rights only apply to immovable objects in the form of land and building rights only.The problem is that Mortgage Rights can be expressly granted over land rights as referred to in the Mortgage Law. The relationship between Mortgage Rights and other rights, as the object of Mortgage, cannot be disputed, but this issue arises in relation to land rights which are permanent in nature over Management Rights which are still land assets belonging to the East Kalimantan Provincial Government.Whereas the implementation of PP Number 40 of 1996 which regulates Building Use Rights can be used as objects of Mortgage Rights, there is a regulatory dichotomy, because Law Number 4 of 1996 clearly regulates that the objects of Mortgage are Building Use Rights, which come from Property Rights, State Land, and Management rights are not questioned. Likewise, the dichotomy states that it is the object of transition that must receive a recommendation. Keywords: Building Use Rights, Local Government